Immunological Evaluation of IgM And IgG Antibodies and Complement Components C3 and C4 in Thalassemia Patients with Toxoplasma Gondii Infection - H. Sulaiman, Evan; N. Shihab, Raghad; Jabbar Obaid, Ahmed; Abd Temur, Ahmed; A. Alwan, Ahlam (Al-Nahrain Journal of Science, 2025)
Toxoplasmosis is known to be transmissible through blood transfusion, especially from asymptomatic, seropositive individuals during the acute phase. Patients with thalassemia are particularly vulnerable to such opportunistic infections, including Toxoplasma gondii. This study aimed to evaluate the levels of Toxoplasma-specific IgG, IgM, and IgA antibodies, along with complement components C3 and C4, in thalassemia patients with and without toxoplasmosis infection. A significant difference (P < 0.001) was observed in all immunological markers when comparing patient groups to the negative control group. Additionally, both thalassemia groups (with and without toxoplasmosis) showed significant differences compared to the toxoplasmosis-positive control group (P < 0.001). Notably, thalassemia patients with toxoplasmosis exhibited higher levels of Toxoplasma-specific antibodies and altered complement levels compared to thalassemia patients without the infection (P < 0.001). These findings suggest an altered immunological profile in thalassemia patients, particularly when co-infected with T. gondii, highlighting the importance of monitoring such markers in this vulnerable population.